Srečko Kosovel in evropska avantgarda - Vrečko, Janez (Primerjalna književnost, 2005)
The paper explores Kosovel's attitude towards Italian futurism, Balkan zenitism and Russian constructivism. Kosovelćs work as a whole, including his letters and diary entries, makes it clear that he would not follow the Italian "liberated words" (parole in liberta), because to him - being a Slovenian poet, and particularly a Slovenian from the Primorska region - the word was sacred and untouchable. His manifesto "To the Mechanics" is further proof of his guarded attitude towards Marinetti's movement. Similarly, Kosovel rejected Micić's zenitism: he saw it as "playing", whereas he wanted art and life to be about seriousness, about "simultaneously revolutionising meaning and form". So it was only after his friend Grahor had returned from the Soviet Union that he was given a chance - through Russian literary constructivism - to use the principle of "gruzification" and "focalisation", and introduce his famous cons poems, which combine revolutionary form with recognisable meanings. His aim was to publish them in a specialised magazine KONS, that he himself would edit and publish. In the summer of 1925 he experienced "a shift to the left" and began to create a different, "constructive" poetry. It was intended for publication by a proletarian publishing house, which he would call Strelci (Shooters). These plans were cutshort by his untimely death at 22. Today, his cons poems are unique, and represent one of the pinnacles of European literary constructivism.
Keywords: Kosovel, Srečko, 1904-1926; Literarne študije; slovenska poezija; evropska avantgarda; konstruktivizem; constructivism